ANALISIS KEBIJAKAN PEMBERIAN PEMBIAYAAN MURABAHAH TERHADAP NON PERFORMING FINANCING MURABAHAH PADA PT BANK MUAMALAT INDONESIA TBK CABANG PONTIANAK - B51109060, Rahman Sastrawan (Jurnal KIAFE, 2013)
This study aimed to determine whether granting murabaha financing policies are applied to PT Bank Muamalat Indonesia, Tbk Pontianak Branch has done well to reduce financing problems. The method used is descriptive method is a method for describing the solution to the problem of the study, carried out data collection techniques are interview techniques, study documentation and Librarianship. Data analysis tools use quantitative analysis, Organizational Structure, Flowchart, Internal Control Questionnaire, and the Compliance Test. Based on the results of research conducted, the authors conclude that policy through the provision of financing murabaha financing systems and procedures in PT Bank Muamalat Indonesia, Tbk Branch Pontianak is good and adequate. From the analysis of the implementation of internal control that the results obtained by 93% murabaha financing systems and procedures work well and effectively. The increase in non-performing financing which are caused by external factors of the customer is not able to restore the murabaha financing which has been given by PT Bank Muamalat Indonesia, Tbk Branch Pontianak.